2017
DOI: 10.2106/jbjs.17.00421
|View full text |Cite
|
Sign up to set email alerts
|

What’s New in Musculoskeletal Infection: Update Across Orthopaedic Subspecialties

Abstract: Specialty Update has been developed in collaboration with the Board of Specialty Societies (BOS) of the American Academy of Orthopaedic Surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Several previous studies have reported that a shorter duration of symptoms was related to the eradication of infection ( 28 31 ). Surgical debridement and subsequent continuous antibiotics may remove planktonic bacteria and younger biofilm ( 32 ). A longer duration of symptoms theoretically indicates higher rates of biofilm formation and may explain why a longer duration of symptoms infers higher failure from DAIR.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported that a shorter duration of symptoms was related to the eradication of infection ( 28 31 ). Surgical debridement and subsequent continuous antibiotics may remove planktonic bacteria and younger biofilm ( 32 ). A longer duration of symptoms theoretically indicates higher rates of biofilm formation and may explain why a longer duration of symptoms infers higher failure from DAIR.…”
Section: Discussionmentioning
confidence: 99%
“…Although two-stage exchange 52 has long been considered the gold standard treatment strategy for chronic PJI in the United States, failure rates up to 30% have been reported. [53][54][55][56][57] With the goal of improving these outcomes and minimizing reinfection, some studies have evaluated EOAP after exchange arthroplasty (Table 1).…”
Section: Extended Oral Antibiotic Prophylaxis After Successful Treatm...mentioning
confidence: 99%
“…A 2-stage revision involves the removal of all implants, irrigation and debridement of all infected tissues, implantation of an antibiotic-impregnated spacer, parenteral administration of microorganism-directed antibiotics for 6 weeks, and reimplantation when the initial infection is deemed to have been adequately treated [ [15] , [16] , [17] , [18] ]. Despite this extensive process, failure rates as high as 34% have been reported, and the etiologies of failures secondary to infection remain unknown [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%